AntiThyroglobulin Antibody as a Prognostic Factor to Evaluate the Recurrence and Metastases of Differentiated Thyroid Carcinoma following Radioactive Iodine Ablation - Yeasmin, Shamima; Begum, Shahnaz; Begum, Fatima (Bangladesh Journal of Nuclear Medicine, 2022)
Objectives: Patients with Differentiated Thyroid Carcinoma (DTC) are usually treated with thyroidectomy followed by radioactive iodine ablation (RAIA). After treatment, during their follow up period, serum thyroglobulin (Tg) estimation and diagnostic whole body 131I scan (DxWBS) are established modalities to observe recurrence. The aim of this study was to evaluate the clinical significance of TgAb levels for possible use as a prognostic factor of recurrence and metastases of disease. Patients & Methods: An observational Cohort study was conducted in total 48 diagnosed DTC patients who underwent total thyroidectomy followed by RAIA during July, 2016 to June, 2017 at National Institute of Nuclear Medicine & Allied Sciences (NINMAS). Among them, 24 patients with high TgAb level (>40 IU/ml) were considered as group I and 24 DTC patients with low TgAb level (<40 IU/ml) was considered as group-II. Detail history, clinical examination, Tg & anti TgAb levels were assessed and DxWBS were done in all patients. Fine needle aspiration cytology (FNAC) of enlarged lymphnodes and 18Fluorine- fluorodeoxyglucose positron emission tomography-Computed Tomography (18F-FDG PET-CT) were done in patients with negative DxWBS but having high anti TgAb. Demographic and clinicopathological characteristics were compared between two groups and recurrence and metastases were observed. Statistical analysis was done. Results: Among 24 patients of Group-I, 6 patients showed either metastases or recurrences and no patient of group-II showed metastasis or recurrence. The difference was statically significant (p<0.05) between two groups. Relative risk (RR) was found 2.33 in group-I in comparison to group-II, suggesting the patients at higher risk of metastases or recurrence in group-I than group-II who had high anti TgAb. Conclusion: Among DTC with high TgAb patients, papillary carcinoma was more common. Recurrence and metastases were evaluated in 6(25%) patients who had high antiTgAb level and 0% with low anti TgAb levels. This may be concluded that, high TgAb levels in patients with DTC could be considered as a marker to evaluate recurrence and metastases after RAIA. Patients of DTC with high TgAb are at risk of recurrence and metastases during follow up period as the RR was found 2.33. Bangladesh J. Nuclear Med. 23(1&2): 9-14, 2020